Uracil derivatives as HIV-1 capsid protein inhibitors: design, in silico, in vitro and cytotoxicity studies. Issue 27 (13th June 2022) - Ramesh, Deepthi; Mohanty, Amaresh Kumar; De, Anirban; Vijayakumar, Balaji Gowrivel; Sethumadhavan, Aiswarya; Muthuvel, Suresh Kumar; Mani, Maheswaran; Kannan, Tharanikkarasu
Abstract : The paper describes the design, synthesis, computational and biological validation of a series of novel uracil derivatives as effective HIV capsid protein inhibitors. Abstract : A series of novel uracil derivatives such as bispyrimidine dione and tetrapyrimidine dione derivatives were designed based on the existing four-point pharmacophore model as effective HIV capsid protein inhibitors. The compounds were initially docked with an HIV capsid protein monomer to rationalize the ideas of design and to find the potential binding modes. The successful design and computational studies led to the synthesis of bispyrimidine dione and tetrapyrimidine dione derivatives from uracil and aromatic aldehydes in the presence of HCl using novel methodology. The in vitro evaluation in HIV p24 assay revealed five potential uracil derivatives with IC50 values ranging from 191.5 μg ml −1 to 62.5 μg ml −1 . The meta -chloro substituted uracil compound 9a showed promising activity with an IC50 value of 62.5 μg ml −1 which is well correlated with the computational studies. As expected, all the active compounds were noncytotoxic in BA/F3 and Mo7e cell lines highlighting the thoughtful design. The structure activity relationship indicates the position priority and lower log P values as the possible cause of inhibitory potential of the uracil compounds.